HUBUNGAN KEPATUHAN ANTENATAL CARE (ANC) DENGAN TERJADINYA PRE-EKLAMSIA - Evin Noviana Sari Evin Noviana Sari (Fakultas Ilmu Kesehatan Universitas Dharmas Indonesia, 2021)
Antenatal care is a program that plans in the form of observation, education, and medical treatment of pregnant women, obtaining a safe and satisfying pregnancy and delivery process. Pre-Eclampsia is hypertension that occurs after 20 weeks of pregnancy. Pre-Eclampsia is followed by the onset of hypertension along with urinary protein and edema due to pregnancy after 20 weeks of gestation or immediately after delivery. This study aimed to determine the relationship between adherence antenatal care and the occurrence of Pre-Eclampsia. This study used an analytic survey method with a cross-sectional approach. The sample was 34 pregnant women. The results of the study found that there was no significant relationship between adherence to antenatal care (ANC) and the occurrence of Pre-eclampsia. This study concluded that most pregnant women adhere to adherence to antenatal care (ANC) and a small proportion of pregnant women do not experience Pre-Eclampsia.